Spending profiles of sultan idris education university undergraduates: a CHAID-based segmentation - Khalid, Khalizul; Ismail, Rosmini (International Business Education Journal, 2019)
Issues on college students spending behaviour have been studied numerous times due to improper use of education funds. Various studies examined determinant factors for this misbehaviour in order to understand, identify and recommend ways to educate these future generations. Some documented relationships between financial behaviours and financial literacy, money beliefs and socialization agents. This study walks the same path but focuses on spending behaviour rather than financial behaviour and examines its association with determinant factors by means segmentation analysis. The aim of the study is to profile Sultan Idris Education University undergraduates’ according to their spending using a decision tree analysis procedure called Chi-squared Automatic Interaction Detector (CHAID). CHAID generates predictive tree models by segmenting based on predictor variables which include demographic characteristics, program of study related traits and funding aspects that were utilized to profiles students’ spending. Spending in this study excludes most incurred expenditures namely living and subsistence costs. Spending profiles were determined based on 751 feedbacks received from business students of Sultan Idris Education University. It was found that, top five most incurred non-subsistence expenses were personal hygiene products, study materials, telecommunications services, clothing and health products. Interestingly, all these five types of spending can be segmented according to only one predictor variable namely, faculty. It can be assumed from this results that, spending profiles are shared within the same faculty. Since spending profiles can be differentiated between faculties, it can be recommended that education programs directed at influencing spending behaviour should be tailor-made according to faculties.